AKTIVITAS AMILASE PENDEGRADASI PATI MENTAH DARI BAKTERI AIR SUNGAI KARANG MUMUS - Astuti, Winni; Adawiyah, Rabiatul; Pratiwi, Djihan Ryn (JURNAL ATOMIK, 2025)
Raw starch degrading amylase (RSDA) is an enzyme that can degrade raw starch into glucose without going through the gelatinization process. This research was conducted to isolate RSDA producing bacteria originating from the Karang Mumus River in Samarinda City. Bacterial isolation was carried out using the spread plate method. Screening for RSDA producing bacteria using nutrient media containing raw starch. The results of bacterial isolation obtained 14 single colonies of bacteria. A total of 5 bacterial colonies out of 14 bacteria were able to produce RSDA. Then the RSDA enzyme from the 5 bacteria was tested for amylase activity quantitatively using the dinitrosalicylic acid (DNS) method. Then, of the 5 bacteria, 1 bacterium with the colony code KM 5 had the highest activity, namely 0,332 U/mL.